2011 IEEE Global Telecommunications Conference - GLOBECOM 2011 2011
DOI: 10.1109/glocom.2011.6134255
|View full text |Cite
|
Sign up to set email alerts
|

Packet Length Adaptation in WLANs with Hidden Nodes and Time-Varying Channels

Abstract: Abstract-In a wireless local area network (LAN), packets can be lost due to a multitude of reasons. It is possible to reduce the probability of occurrence of some of these loss mechanisms by reducing packet length at the medium access control (MAC) layer. However, there is an inherent tradeoff in that shorter packets decrease efficiency with respect to overhead. In current packet length adaptation literature, simplified or incomplete packet loss models are used, neglecting channel fading or collisions due to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Krishnan et al [21] apply a complete packet loss model and propose a local packet length adaptation algorithm whereby each node dynamically adjusts its packet length based on estimates of the probabilities of each significant type of packet loss. In their technique, the access point periodically broadcasts channel occupancy information, which each node uses in conjunction with its own local observations in order to estimate current network conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Krishnan et al [21] apply a complete packet loss model and propose a local packet length adaptation algorithm whereby each node dynamically adjusts its packet length based on estimates of the probabilities of each significant type of packet loss. In their technique, the access point periodically broadcasts channel occupancy information, which each node uses in conjunction with its own local observations in order to estimate current network conditions.…”
Section: Related Workmentioning
confidence: 99%
“…The channel feedback can be avoided by implicitly relying on first packet ACKs in packet bursts [3] using the TXOP extension in 802.11e/n networks. An extension to [2] that considers packet length adaptation to maximise link throughput is presented in [4]. It relies on a joint packet length optimisation over MAC collisions and channel errors.…”
Section: Related Workmentioning
confidence: 99%
“…We have also demonstrated the accuracy of our proposed estimation method via NS-2 simulations. Furthermore we have shown that these probability estimation techniques can be used to improve overall throughput by as much as 25% via packet length adaptation [10], 50% via carrier sense threshold adaptation [11], and 400% via modulation rate adaptation [9].…”
Section: Introduction and Related Workmentioning
confidence: 99%